Hambatan Komunikasi Antar Budaya dalam Penerjemahan di Perusahaan Modal Asing Jepang - Luthfiyah, Ulfi Zakiyah (Universitas Semarang, 2016)
This study aims to find out the barriers of intercultural communication that occurs in the Japanese translation - Indonesian and vice versa in PT. METEC Semarang, which is the capital of Japan's foreign companies. The theory used in this study are speech codes theory, where acts of communication is not only seen from the spoken words alone, but cultural background, facial expressions, gestures, intonation is a unity that would give meaning to the act of communication. The results of this study indicate that there are two obstacles, namely the translation of external factors and internal factors. External factors consist of technical terms and new terms, length of utterance, speaking speed, and tone of voice. Internal factors consist of cognitive factors, namely speed and vocabulary to understand the message, and psychological factors are anxiety is high.